Exploring the Association Rules of Road Traffic Accidents - Sukprasert, Anupong; Tosasukul, Jiraroj; Sangutai, Taradon (Journal of Science Ladkrabang, 2023)
In this research, the objective is to extract patterns of road traffic accidents in Thailand using association rules and the FP-growth algorithm was employed to mine frequent patterns. The road accident data in Thailand used in this study was collected from Information and Communication Technology Center, Office of the Permanent Secretary of the Ministry of Transport between January 1, 2019 and September 30, 2022, with a total of 74,231 instances and 10 attributes included time, month, provinces, weather, types of cars, accident causes, accident form, road characteristics, road types, and results of accidents. The association analysis results on Thailand road traffic accidents showed that the most common patterns of road traffic accidents were rear-end collisions, rollovers, and falls onto the road. The speed limit violation led to the collision. Accidents are more likely to occur when the road is straight and no slope, and clear weather. Furthermore, the most common types of vehicles engaged are motorcycles, while the roads of the Ministry of Highway were the scene of the most collisions.